Impact of dietary supplementation with biological zinc, selenium nanoparticles, and their combination on growth, carcass characteristics, blood parameters, and meat quality in broiler chickens. - Alhasani, Reem Hasaballah (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: This study examined the impacts of feeding zinc and selenium (SeNPs) nanoparticles and their combinations (ZnNPs and SeNPs and ZnNPs + SeNPs) on growth efficiency, the carcass, blood indicators, and meat criteria traits in chickens during 38 days. Materials and Methods: Two hundred forty (Cobb 500) 7-day-old chicks were divided in entirely random form into 4 groups, each group divided into 6 replicates of 10 chicks. Dietary supplements were given in accordance with a corn-soybean diet in the following 4 test treatments: 0.0 (T0), 1.5 mg/kg SeNPs(T1), 2.0 mg/kg ZnNPs(T2), and 1.5 mg/kg SeNPs + 2.0 mg/kg ZnNPs(T3). Water and feed were provided at all times during the 38-day period. Results: The findings concluded that the mixing of SeNPs, ZnNPs, or its combination as feed addition improved rates of growth, as illustrated by higher “body weight” and reduced “feed intake and feed conversion ratio”. The results indicated that there were no appreciable variations (p ≤ 0.05) in carcass measurements between the treatments. Additionally, hematological markers showed significant improvements, with decreased amounts of “uric acid, creatinine, aspartate aminotransferase, alanine aminotransferase, total cholesterol, and low-density lipoprotein”, while high-density lipoprotein values increased in chicks feeding ZnNPs or SeNPs compared to the control group in eating. Additionally, T3 levels were lowered and T4 levels were raised when SeNPs, ZnNPs, or a mixture of the two were given. Additionally, these treatments affected immunological responses, leading to increased immunoglobulin (IgM and IgG) levels. By increasing moisture quantity while maintaining carcass texture, aroma, tenderness, juiciness, and acceptability scores, these supplements also had an impact on meat quality. Conclusion: The addition of SeNPs and ZnNPs to the chicken diet enhanced immune system function, growth, and blood criteria. This raises the possibility of a substitute for popular growth boosters and organic immune modulators. J. Adv. Vet. Anim. Res., 12(2): 539–548, June 2025 http://doi.org/10.5455/javar.2025.l918